Pengaruh Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), dan Price to Book Value (PBV) terhadap Harga Saham Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2022 - Putri Aprilia; Tutut Dewi Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to evaluate the impact of ROA, CR, DER, and PBV on the stock prices of technology companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022. The research is quantitative with a descriptive approach, utilizing secondary data from the BEI website. The population consists of 38 companies, with a purposive sample of 26 technology companies. Analytical methods include descriptive statistics, classic assumption tests (normality, multicollinearity, autocorrelation, and heteroskedasticity), multiple linear regression, and hypothesis testing using the t-test. The study results indicate that ROA, CR, and PBV significantly affect stock prices (p < 0.05), while DER does not have a significant impact (p > 0.05).